The socio-legal relevance of the social function of property: recognition of new needs and integrated inter-institutional action (Research, Society and Development, 2021)
Urban policy is the set of measures that aim to organize living spaces, organizing all areas in which human beings carry out social activities and all property, without exception, respecting the owner's right, must fulfill its social function. Most municipalities in the state of Goiás face the problem of informal urban growth with irregular constructions and illegal settlements, for example. In Goiás, the permanent land regularization program was created with the objective of legalizing illegally occupied areas “Casa Legal”. This article is a qualitative-based case study that analyzes the implementation of the program in Parque das Brisas in Caldas Novas’ municipality of GO, where the policy of land regularization of social interest was adopted in order to donate property titles to its residents through the process of legalizing areas of social interest. Results show when there is an integration of public and private interests, the legal system can determine prohibition of abusive use of property. The process took place with specific approaches, integrated and complementary to each other, involving inter/multidisciplinary aspects such as land tenure, search for documents of existence of the land, succession chain, existing plants and records, in order to enable land titling.